A cost-minimization analysis of combination therapy in hypertension: fixed-dose vs extemporary combinations - Bellone, Marco; Sbarra, Pierluigi (Farmeconomia. Health economics and therapeutic pathways, 2013)
BACKGROUND: Cardiovascular disease management and prevention represent the leading cost driver in Italian healthcare expenditure. In order to reach the target blood pressure, a large majority of patients require simultaneous administration of multiple antihypertensive agents. OBJECTIVE: To assess the economic impact of the use of fixed dose combinations of antihypertensive agents, compared to the extemporary combination of the same principles. METHODS: A cost minimization analysis was conducted to determine the pharmaceutical daily cost of five fixed dose combinations (olmesartan 20 mg + amlodipine 5 mg, perindopril 5 mg + amlodipine 5 mg, enalapril 20 mg + lercanidipine 10 mg, felodipine 5 mg + ramipril 5 mg, and delapril 30 mg + manidipine 10 mg) compared with extemporary combination of the same principles in the perspective of the Italian NHS. Daily acquisition costs are estimated based on current Italian prices and tariffs. RESULTS: In three cases the use of fixed‑dose combination instead of extemporary combination induces a lower daily cost. Fixed combination treatment with delapril 30 mg + manidipine 10 mg induces greater cost savings for the National Health System (95,47 €/pts/year), as compared to free drugs combination therapy. CONCLUSIONS: Compared with free drug combinations, fixed‑dose combinations of antihypertensive agents are associated with lower daily National Health Service acquisition costs.